Improvement of bioethanol production from water hyacinth biomass by optimization of fermentation process conditions using response surface methodology - Saleigzer Abay Aragaw; Temesgen Atnafu Yemata; Adane Adugna Ayalew; Asab Alemneh Tadesse; Asmarech Yeshaneh Fekad; Alemayehu Keflu Shibesh; Fentahun Adamu Getie; Tegen Dagnew Tessema; Tessera Alemneh Wubieneh (Discover Applied Sciences)
Abstract Energy generation via conversion of agro-industrial wastes is a novel approach for waste management and valorization which offers socioeconomic advantages and minimizes exhaust emissions. In this study, optimization of fermentation conditions in bioethanol production from water hyacinth (WH) (Eichhornia crassipes) was examined by employing Saccharomyces cerevisiae. An experimental design was performed based on Central Composite Design (CCD) with response surface methodology. This CCD method was employed to optimize and evaluate the interaction effects of fermentation conditions (media pH (4–6), inoculum size (1–10 v/v %), and fermentation time (48–96 h.). The statistical analysis result indicated that the model of WH ethanol demonstrated to be extremely significant with very small probability values of < 0.0001. The optimum conditions attained were fermentation time of 74.38 h., inoculum size of 7.33 (%v/v), and pH of 4.63. This resulted in ethanol yield of 38.73% (v/v) and final ethanol titer of 28.7 g/L. Hence, this study confirms that WH is a potential feedstock for production of bioethanol.